As contribuições da disciplina metodologia do ensino de literatura em libras para alunos surdos na UFAM - Albuquerque, Deuziane Menezes (Brasil, 2024)
The research aims to analyze the impacts of the subject Methodology for teaching Literature in Libras on the learning process of Deaf Culture artifacts for deaf students at UFAM. According to Karnopp (2006), Deaf Literature has been consolidating itself as a form of artistic and sociocultural expression for the Deaf community. The study uses a qualitative approach, with bibliographical analysis of works that address the topic. The questionnaire was applied to deaf students who studied the Literature Methodology in Libras discipline at the Federal University of Amazonas UFAM. In view of this, we believe that the discipline proposes the development of deaf identity and its subjectivity, also the importance of knowledge at the University being taken to schools and the fundamental role of the family in access to Deaf Literature for the deaf.